The effects of dietary selenium and vitamin E and their combination on the fatty acids of erythrocytes, bone marrow and spleen tissue lipids of lambs - Yilmaz, O; Celik, S; Naziroglu, M; Cay, M; Dilsiz, N (John Wiley & Sons Ltd, 1997)
The object was to determine the influence of dietary vitamin E, selenium and their combination on the fatty acid content of erythrocytes, bone marrow and spleen lipids of Akkaraman lambs. After supplementation for 15 days, the amount of all fatty acids was slightly higher (p < 0.05) in the vitamin E as compared to the control group, whereas the amount of longer fatty acids was significantly higher (p < 0.01, p < 0.001)in the selenium and combination groups. On the thirtieth day, the amount of all fatty acids was slightly high (p < 0.5) in all the supplemented groups in comparison with the control group. In the bone marrow lipids, the amount of longer fatty acids was decreased (p < 0.05, p < 0.01, p < 0.001) in the Vitamin E and combination groups as compared to the control. Although the amount of some fatty acids was high (p < 0.05, p < 0.01) in the selenium group compared to the control, linoleic (18:2), linolenic (18:3) and the polyunsaturated fatty acids (PUFA) were lower (p < 0.05, p < 0.001). In the spleen lipids, the amount of longer fatty acids was slightly decreased (p < 0.05) in the vitamin E group as compared with the control; however the amount of longer fatty acids was significantly higher (p < 0.05, p < 0.01) in the selenium and combination groups in comparison to the control group. Thus dietary supplementation with selenium was more effective than dietary vitamin E supplementation in altering the fatty acid content of the erythrocyte, bone marrow and spleen lipids. ((C) 1997 by John Wiley & Sons, Ltd.)
Keywords: dietary vitamin E and selenium; erythrocyte; bone marrow; spleen; fatty acid content; lambs